Impact of 1, 8-diiodooctane on the morphology of organic photovoltaic (OPV) devices – A Small Angle Neutron Scattering (SANS) study. (February 2020) - Bernardo, Gabriel; Gaspar, Hugo; Pérez, Gabriel E.; Shackleford, Alec S.D.; Parnell, Andrew J.; Bleuel, Markus; Mendes, Adélio; King, Stephen M.; Parnell, Steven R.
Abstract: The impact of the additive 1, 8-diiodooctane on the morphology of bulk-heterojunction solar cells based on the systems P3HT:PC71 BM, PTB7:PC71 BM and PTB7-Th:PC71 BM is studied using a combination of Small Angle Neutron Scattering (SANS) and Atomic Force Microscopy (AFM). The results clearly show that while in the P3HT:PC71 BM system, the additive DIO promotes a slight coarsening of the phase domains (type I additive), in the systems PTB7:PC71 BM and PTB7-Th:PC71 BM, DIO promotes a large decrease in the size of the phase domains (type II additive). SANS is demonstrated as being particularly useful at detecting the minor morphological changes observed in the P3HT:PC71 BM system, which can be hardly seen in AFM. This work illustrates how SANS complements AFM and both techniques when used together provide a deeper insight into the nanoscale structure in thin organic photovoltaic (OPV) device films. Highlights: SANS was used to study the impact of the additive DIO on the active layer morphology of polymer solar cells. In the P3HT:PC71 BM system, the additive DIO promotes a slight coarsening of the phase domains (type I additive). In the systems PTB7:PC71 BM and PTB7-Th:PC71 BM, DIO promotes a large decrease in the size of the phase domains (type II additive). A comparison between the SANS and AFM techniques was performed and their complementarity was demonstrated. SANS proved very useful for probing a few nanometre changes in the size of the phase domains which can hardly be seen in AFM.